Pelatihan Building Information Modeling kepada Praktisi Konstruksi di Kalimantan Selatan - Irfan Prasetia; Darmansyah Tjitradi; Husnul Khatimi; Jovana Neilkelvin; M. Rijalul Fikri .A. (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
Due to the rapid developments in the current digitalization era, information technology has affected almost every aspect of life. In the construction world, the influence of developments in information technology has led to the emergence of a building database concept called Building Information Modeling (BIM). The Ministry of Public Works and Housing has issued Ministerial Regulation Number 22/PRT/M/2018 and strengthened by PP Number 16 of 2021 regarding the implementation of BIM. Thus, the application of BIM in building projects, especially those owned by the government, has become necessary. Therefore, it is important to carry out BIM training to prepare human resources (HR) who can use BIM-based building design software. The BIM training was held in collaboration with the Human Settlements section of the Public Works and Spatial Planning Agency (PUPR Agency) of South Kalimantan Province. The participants were not only workers of the PUPR Agency but also construction practitioners in the South Kalimantan Province. From the pre-test results, it can be seen that the participants still lack understanding and mastery of BIM software. Meanwhile, after the BIM training was held, there was a significant increase in the participants' mastery and understanding based on the post-test results.